Edmodo in semi-technical English courses: towards a more practical strategy for language learning/practice. Issue 7 (3rd September 2022) - Nami, Fatemeh
Abstract: This study applied Edmodo as a supplementary environment for additional language practice in a semi-technical English course in an EFL context, with a quasi-experimental between-subjects (control versus experimental group) design. In addition to conventional classroom instruction and practice, the experimental group practiced additional language exercises using Edmodo application while the control group participants worked on similar exercises during extended classroom meetings. The results of paired and independent sample t-tests conducted on both groups' using 48-item, multiple-choice (vocabulary, grammar, and reading comprehension) pre and posttests revealed that while both groups demonstrated a statistically significant performance in the achievement posttest which was administered at the end of the course, the performance of the experimental group was significantly better than the control. The findings suggest that Edmodo is a valuable and cost-effective tool for language learning/practice beyond the physical and temporal confinements of conventional language classrooms.